2012
DOI: 10.2519/jospt.2012.3579
|View full text |Cite
|
Sign up to set email alerts
|

The Scapular Assistance Test Results in Changes in Scapular Position and Subacromial Space but Not Rotator Cuff Strength in Subacromial Impingement

Abstract: Study Design Controlled laboratory study. Objectives To determine the effect of the modified scapular assistance test (SAT) on 3-dimensional shoulder kinematics, strength, and linear measures of subacromial space in patients with subacromial impingement syndrome (SAIS). Background Abnormal scapular kinematics have been identified in patients with SAIS. Increased scapular upward rotation and posterior tilt, as induced with manual assistance using the SAT, have been theorized to increase subacromial space and ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
39
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(42 citation statements)
references
References 49 publications
3
39
0
Order By: Relevance
“…The testers undertaking the ultrasound scanning were physiotherapists in seven of the studies,7–9 24 26 31 32 variously described as having training ranging from 1 hour to 3 months, and radiologists in two of the studies,23 30 with one study not providing details of the raters 25. One study reported similar degrees of reliability between an experienced radiologist (ICC=0.94) and a novice in ultrasound (ICC=0.92),30 while in two studies by the same authors, one using a physiotherapist trained in shoulder ultrasound, and the other using student physiotherapists with limited training or experience, slightly better reliability was reported with the experienced examiner (ICC=0.96–0.99)26 compared with the novices (ICC=0.88–0.91) 27…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The testers undertaking the ultrasound scanning were physiotherapists in seven of the studies,7–9 24 26 31 32 variously described as having training ranging from 1 hour to 3 months, and radiologists in two of the studies,23 30 with one study not providing details of the raters 25. One study reported similar degrees of reliability between an experienced radiologist (ICC=0.94) and a novice in ultrasound (ICC=0.92),30 while in two studies by the same authors, one using a physiotherapist trained in shoulder ultrasound, and the other using student physiotherapists with limited training or experience, slightly better reliability was reported with the experienced examiner (ICC=0.96–0.99)26 compared with the novices (ICC=0.88–0.91) 27…”
Section: Resultsmentioning
confidence: 99%
“…There was variation in transducer placement, with two studies placing it on the anterior part of the acromion,23 31 while others used the posterior or mid-acromion25 or did not give adequate details of the testing protocol. There were also differences in how AHD was measured between studies.…”
Section: Resultsmentioning
confidence: 99%
“…↓PT and ER at 90° abduction. (9) ICC ( (12) ICC ( CG Mell et al (2005) (13) SD for phases 1, Group Group Group FSG compared to CG Rundquist et al (2003) (15) ------↓ Maximum ROM of arm elevation from flexion to scapular plane abduction to coronal plane abduction. ↑ ER ROM with the abducted arm than with the arm at the side.…”
Section: A: Sis Groupmentioning
confidence: 97%
“…Manual therapy, 13(6), 544-551. Yoshizaki, K., Hamada, J., Tamai (15) Ogston & Ludewig (2008) ( (19) -------3 ASI, 2 MDI 1 SI -------37 ± 8.5 ------ (21) recent upper extremity pathology Arias (22) 25 40 (1) Static 90˚ Seitz & Michener (2012) (9) Static Sc Emag Acromial receiver -Skin fixed Pro/lat/tilt AA?? 90˚…”
Section: Stmdsmentioning
confidence: 97%
“…Previous studies measured AHD with the shoulder in a resting neutral position 8,16 as well as active or passive shoulder abduction at 45°and 90°a rm elevation. [22][23][24] Such studies have reported that the shoulder position might affect the reliability of AHD measurement. 17 Superior humeral migration occurs in healthy individuals as the shoulder abducts from 0 to 90°.…”
Section: Introductionmentioning
confidence: 99%